The natural logarithm of a number is defined as follows:
![\ln A=x_{}](https://img.qammunity.org/2023/formulas/mathematics/college/gahpe2vyql8dnljb9jktdhxyg5mz8gdmho.png)
means that when we elevate the Euler number e to x, the result is A:
![\ln A=x\Rightarrow A=e^x](https://img.qammunity.org/2023/formulas/mathematics/college/rv3tklv99nv0s3tbjwmd4lojuwth4sofxy.png)
In this problem, we have
![A=e^(-3)](https://img.qammunity.org/2023/formulas/mathematics/college/8bvr983ss3024ps212g2bbasmx1501x5kl.png)
Thus
![\ln e^(-3)=x\Rightarrow e^(-3)=e^x](https://img.qammunity.org/2023/formulas/mathematics/college/ucue3s7f5ddwcyt8mjfu6xrphx9ye3gm5e.png)
Then, since the bases are the same, for the equation to hold we need the exponents to be the same:
![\begin{gathered} e^(-3)=e^x\Rightarrow-3=x \\ \\ \therefore x=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6drnz8fwwazsvjmjcasjd4t5gyq1q7mc10.png)